Measurement of Antioxidant Effects on the Auto-oxidation Kinetics of Methyl Oleate – Methyl Laurate Blend as a Surrogate Biodiesel System - Tjokorde Walmiki Samadhi; Toshihiro Hirotsu; Shinichi Goto (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
This research investigates the feasibility of methyl oleate-methyl laurate blend as a surrogate biodiesel system which represents jatropha-coconut oil biodiesel, a potentially suitable formulation for tropical climate, to quantify the efficacy of antioxidant additives in terms of their kinetic parameters. This blend was tested by the Rancimat EN14112 standard method. The Rancimat tests results were used to determine the primary oxidation induction period (OIP) and first-order rate constants and activation energies. Addition of BHT and EcotiveTM antioxidants reduces the rate constants (k, h-1) between 15 to 90% in the 50-200 ppm dose range, with EcotiveTM producing significantly lower k values. Higher dose reduces the rate constant, while oleate/laurate ratio produces no significant impact. Antioxidants increase the oxidation activation energy (Ea, kJ/mol) by 180 to almost 400% relative to the non-antioxidant value of 27.0 kJ/mol. EcotiveTM exhibits lower Ea, implying that its higher efficacy stems from a better steric hindrance as apparent from its higher pre-exponential factors. The ability to quantify oxidation kinetic parameters is indicative of the usefulness of methyl oleate-laurate pure FAME blend as a biodiesel surrogate offering better measurement accuracy due to the absence of pre-existing antioxidants in the test samples.